Antifungal activity of alexidine dihydrochloride in a novel diabetic mouse model of dermatophytosis - Nabeela, Sunna; Date, Abhijit; Ibrahim, Ashraf S.; Uppuluri, Priya (Frontiers in Cellular and Infection Microbiology, 2022)
Dermatophytosis is one of the most prevalent fungal infections worldwide, and a major public health problem. Recent years have seen a change in the epidemiological patterns of infecting fungi, corresponding with an alarming rise in the prevalence of drug recalcitrant dermatophyte infections. In patients with diabetes mellitus, dermatophytosis is more severe and recurrent. It is important that the potency of promising new antifungal drugs in the pipeline be expanded to include dermatophytosis. To facilitate this effort, we established a clinically pertinent mouse model of dermatophyte infections, wherein diabetic mice were infected with Trichophyton mentagrophytes on abraded skin. The diabetic mouse model was optimized as a simple and robust system simulating dermatophytoses in diabetic patients. Outcome of infection was measured using clinical and mycological parameters. Infected mice with fungal lesions were treated with oral and topical formulations of terbinafine, or topical administration of the FDA-approved and repurposed pan-antifungal drug alexidine dihydrochloride (AXD). In this model, AXD was found highly efficacious, with outcomes comparable to the standard of care drug terbinafine.